Mechanical Properties of Injection Molded Recycled High Density Polyethylene (rHDPE) Blends with pellets Low Density Polyethylene (pLDPE) - Muhammad Dzulfikar; Sri Mulyo Bondan Respati; Muhammad Nasikin (Universitas Wahid Hasyim, 2022)
Recycling polymer has become a mandatory for sustainable development goals, life beyond water and land. Therefore, recycled polymer blends containing rHDPE/pLDPE (high density polyethylene and low density polyethylene) with composition 100/0, 80/20, 70/30, 50/50, 40/60, 30/70, and 0/100 have been prepared by melt compounding method using injection molding at 200 oC. Tensile testing shows that there is strong combination between rHDPE/rLDPE blends. Elongation at break differ from 122-230% and density test give results around 1.1 g/cm3. Injection molding process with the proper temperature setting and mixing of crushed plastic also affects the ductility, flexibility, brittleness and hardness of the specimen